Pola penggunaan antibiotik infeksi saluran pernapasan atas akut pada anak - Angin, Martianus Perangin; Saputri, Gusti Ayu Rai; Pangestu, Dimas Aji (JOURNAL OF Pharmacy and Tropical Issues, 2025)
Patterns of antibiotic use of acute upper respiratory treatment in children Background : Acute upper respiratory tract infections cause inflammation and infection of the nose and throat. The selection of antibiotics should be based on information about the cause of infection, results of microbiological examinations, pharmacokinetic and pharmacodynamic profiles of antibiotics. Purpose : To determine the pattern of use of antibiotics for acute upper respiratory tract infections in children at the Sukadana Regional General Hospital, East Lampung Regency with the right parameters for diagnosis, right indication, right patient, right drug, right dose. Method : Descriptive observational, the data is done retrospectively using the patient's medical record. Results : Showed the highest prevalence, namely: at the age of children (6-12 years) as many as 11 patients (52%), female sex as many as 11 patients (52%), on the antibiotic Amoxicillin as many as 13 cases (62%). Conclusion : From the rationale analysis of the use of antibiotics in children with acute upper respiratory tract infections, it was obtained: Correct Diagnosis 100%, Correct Indication 100%, Correct Patient 100%, Correct Drug 100%, Correct Dose 100%  Keywords : Acute Upper Respiratory Tract Infection; Antibiotics; Rationality. Pendahuluan : Infeksi saluran pernapasan atas akut menyebabkan peradangan serta infeksi pada hidung dan tenggorokan. Pemilihan antibiotik harus berdasarkan informasi tentang  penyebab infeksi, hasil pemeriksaan mikrobiologi, profil farmakokinetik dan farmakodinamik antibiotik. Tujuan : Untuk mengetahui pola penggunaan antibiotik Infeksi Saluran Pernapasan atas Akut pada anak di Rumah Sakit Umum Daerah Sukadana Kabupaten Lampung Timur dengan parameter tepat diagnosis, tepat indikasi, tepat pasien, tepat obat, tepat dosis. Metode : Observasional deskriptif, data dilakukan secara retrospektif dengan menggunaakan rekam medik pasien. Hasil : Menunjukan prevalensi terbanyak yaitu: pada usia anak (6-12 tahun) sebanyak 11 pasien (52%), jenis kelamin perempuan sebanyak 11 pasien (52%), pada obat antibiotik Amoksisilin sebanyak 13 kasus (62%). Simpulan : Dari analisis rasionalitas penggunaan antibiotik pada anak dengan penyakit infeksi saluran pernapasan atas akut di peroleh: Tepat Diagnosa 100%, Tepat Indikasi 100%, Tepat Pasien 100%, Tepat Obat 100%, Tepat Dosis 100%